THE EFFECT OF IRON DEFICIENCY ANEMIA DURING PREGNANCY ON BREASTFEEDING AND MATERNAL MENTAL WELL-BEING - Huolila, Linda (My University, 2020)
In this study we will collect and analyze scientific publications that review the correlation between anemia and breastfeeding, and anemia and maternal mental well-being both prepartum and postpartum. The risks concerning iron deficiency anemia during pregnancy and postpartum are widely known; anemia increases the morbidity of both mother and child. Our aim is to review whether iron deficiency anemia affects the initiation and duration of breastfeeding and, on the other hand, whether it increases maternal depression and anxiety. According to our study, consensus whether anemia affects the initiation and duration of breastfeeding has not been reached. There are only a few studies of the association between postpartum anemia and duration of breastfeeding, and none of the association between anemia during pregnancy and duration of breastfeeding. Further research on the subject is needed. The association between anemia and mental well-being, on the other hand, has been studied widely in the past. The studies concern mostly the association of anemia and postpartum depression. The evidence suggests that especially postpartum anemia is a major risk factor for postpartum depression. We suggest that promotion of maternal health by means of treatment of iron deficiency anemia during pregnancy and postpartum by adequate iron supplementation could be one of the key factors in the prevention of maternal postpartum depression, anemia and possibly also cessation of breastfeeding.
Keywords: iron deficiency anemia, breastfeeding, postpartum depression